Deterioro cognitivo y su influencia en el estado de ánimo del adulto mayor de la Ciudadela Primero de Mayo del cantón Guaranda- Provincia Bolívar - Paredes Caiza, Evelin Mariana (2020)
This research addressed the issue of cognitive impairment and its influence on the mood of the elderly, because the geriatric population is viewed as a forgotten group, priority attention, prone to physical problems, mental, emotional and social, which lead to degenerative diseases associated with inappropriate lifestyles. The main objective of the research was to describe the main effects of cognitive impairment and how it influences mood. A methodology concomitant with the subject was proposed, carrying out clinical interviews and psychometric tools for the elaboration of the psychodiagnostic results. The development of the theoretical perspective was based on the review of academic documentation. According to the analysis, it is concluded that the results achieved are similar to the theory cited in this case study, it was concluded that the patient shows a moderate cognitive deterioration, modifying the cognitive functions such as memory, attention, information retention, thus affecting his quality of life. Thanks to the collection of the information, a therapeutic scheme can be implemented according to the patient's symptoms.